A Novel Procedure for the Immediate Reconstruction of Severely Resorbed Alveolar Sockets for Advanced Periodontal Disease - Mario Aimetti; Valeria Manavella; Luca Cricenti; Federica Romano (Case Reports in Dentistry)
Background. Several clinical techniques and a variety of biomaterials have been introduced over the years in an effort to overcome bone remodeling and resorption after tooth extraction. However, the predictability of these procedures in sockets with severely resorbed buccal/lingual plate due to periodontal disease is still unknown. Case Description. A patient with advanced periodontitis underwent extraction of upper right lateral and central incisors. The central incisor exhibited complete buccal bone plate loss and a 9 mm vertical bone deficiency on its palatal side. The alveolar sockets were filled with collagen sponge and covered with a nonresorbable high-density PTFE membrane. Primary closure was not attained and any rigid scaffold material was not used. Histologic analysis provided evidence of new bone formation. At 12 months a cone-beam computed tomographic scan revealed enough bone volume to insert two conventional dental implants in conjunction with minor horizontal bone augmentation procedures. Clinical Implications. This case report would seem to support the potential of the proposed reconstructive approach in changing the morphology of severely resorbed alveolar sockets, minimizing the need for advanced bone regeneration procedures during implant placement.